A Randomized controlled trial of motivational interviewing + self‐help versus psychoeducation + self‐help for binge eating. Issue 3 (13th January 2014) - Vella‐Zarb, Rachel A.; Mills, Jennifer S.; Westra, Henny A.; Carter, Jacqueline C.; Keating, Leah
ABSTRACT: Objective: Motivational Interviewing (MI) is a collaborative therapy that focuses on strengthening a person's internal motivation to change. Research suggests that MI may be helpful for treating binge eating; however, findings are limited and little is known about how MI for binge eating compares to active therapy controls. The present study aimed to build on current research by comparing MI as a prelude to self‐help treatment for binge eating with psychoeducation as a prelude to self‐help treatment for binge eating. Method: Participants with full or subthreshold DSM‐IV Binge Eating Disorder or nonpurging Bulimia Nervosa were randomly assigned to receive either 60 minutes of MI followed by a self‐help manual ( n = 24) or 60 minutes of psychoeducation followed by a self‐help manual ( n = 21). Questionnaires were completed pre‐ and postsession, and at 1 and 4 months postsession. Results: MI significantly increased readiness to change and confidence in ability to control binge eating, whereas psychoeducation did not. No group differences were found when changes in eating disorder attitudes and behaviors were examined. Discussion: MI offers benefits for increasing motivation and self‐efficacy. However, it may not be a uniquely effective treatment approach for reducing binge eating. © 2014 Wiley Periodicals, Inc. (Int J Eat Disord 2015; 48:328–332)